#PrayForKanjuruhan On Twitter: Public Response to the Kanjuruhan Stadium Disaster - Perdana, Gusti Naufal Rizky; Irawan, Bambang; Akbar, Paisal (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2023)
Social media platforms, such as Twitter, serve as vital channels for disseminating information and expressing opinions on various issues. This research focuses on analyzing the hashtag #PrayForKanjuruhan on Twitter, which emerged in response to the tragic riot at Kanjuruhan Stadium that resulted in numerous fatalities. The study aims to assess the intensity of the conversations associated with this hashtag and to examine the key issues and criticisms expressed within these discussions. Employing a qualitative methodology with the Qualitative Data Analysis (QDA) Miner approach and utilizing Nvivo 12 Plus software, this research conducts network, content, and cloud analyses to understand the discourse surrounding #PrayForKanjuruhan. The results reveal a high level of conversation intensity, reflecting diverse responses from various groups. The predominant focus in the hashtag discussions is on expressing concern for the victims of the tragedy, rather than criticizing the individuals or entities involved in the incident. The findings underscore Twitter’s effectiveness as a platform for users to voice their reactions and engage in discourse related to the Kanjuruhan Stadium disaster. By providing a space for both emotional support and critical discussion, Twitter plays a significant role in shaping public response to such crises.Keywords: Public response, social media, Kanjuruhan Stadium disaster ABSTRAKPlatform media sosial, seperti Twitter, berfungsi sebagai saluran penting untuk menyebarkan informasi dan mengekspresikan pendapat tentang berbagai isu. Penelitian ini berfokus pada analisis tagar #PrayForKanjuruhan di Twitter, yang muncul sebagai respons terhadap kerusuhan tragis di Stadion Kanjuruhan yang mengakibatkan banyak korban jiwa. Studi ini bertujuan untuk menilai intensitas percakapan yang terkait dengan tagar tersebut serta mengkaji isu-isu kunci dan kritik yang diungkapkan dalam diskusi tersebut. Dengan menggunakan metodologi kualitatif melalui pendekatan Qualitative Data Analysis (QDA) Miner dan memanfaatkan perangkat lunak Nvivo 12 Plus, penelitian ini melakukan analisis jaringan, konten, dan cloud untuk memahami wacana yang berkembang di sekitar #PrayForKanjuruhan. Hasil penelitian mengungkapkan tingginya intensitas percakapan, mencerminkan beragam respons dari berbagai kelompok. Fokus utama dalam diskusi tagar ini adalah menyampaikan kepedulian terhadap para korban tragedi, bukan mengkritik individu atau pihak yang terlibat dalam insiden tersebut. Temuan ini menegaskan efektivitas Twitter sebagai platform bagi pengguna untuk menyuarakan reaksi mereka dan terlibat dalam wacana terkait bencana di Stadion Kanjuruhan. Dengan menyediakan ruang untuk dukungan emosional dan diskusi kritis, Twitter memainkan peran penting dalam membentuk respons publik terhadap krisis semacam ini.Kata Kunci: Respon public, media social, bencana Stadion Kanjuruhan